Development and psychometric validation of the Inventory of Drug Use Determinants amongst Iranian University Students (IDUD-US) in Tabriz, Iran. (1st November 2020) - Nikanfar, Reza; Mahmoodi, Hassan; Allahverdipour, Hamid; Asghari-Jafarabadi, Mohammad; Shaghaghi, Abdolreza
ABSTRACT: Objective: To develop and psychometrically testing the Inventory of Drug Use Determinants among University Students (IDUD-US) to ascertain precipitating factors of drug use by the Iranian university students. Methods: The preliminary item pool generated through an extensive literature review and a panel of experts was solicited to assess its face and content validity. The study sample included 214 registered current or former drug users who had initiated the harmful behavior since their student-life. They were recruited through approaching the private/non-private Drug Treatment Centers (DTC) from November 2015 to June 2016 in the greater city of Tabriz, Iran. Results: The s tructural indicators of the Kaiser-Meyer-Olkin (0.725) and Bartlett test of sphericity ( P < .0001) verified interpretability of the exploratory factor analysis (EFA) output. The internal consistency measure of the scale was in the vicinity of acceptable range (α = 0.782). Having an addicted friend, pursuit of pleasure and easy purchasability of illegal substances were main trigger for commencement of drug use by 69.6, 64.5, and 61.7% of the respondents consequently. Conclusion: Psychometric consistency of the constructed instrument was verified for use in Iranian university students.